The New Paradigm of Immunity to Tuberculosis - Divangahi, Maziar.; Divangahi, Maziar. (Advances in Experimental Medicine and Biology,, 2013)
This book illustrates the intimate relationship between alveolar macrophages and Mycobacterium tuberculosis (M.tb.), and the former’s role in both innate and adaptive immunity against M.tb. It covers research done over the last decade. It also explores the role of macrophage death following infection with M.tb. in determining whether successful immunity is stimulated, or whether clinical disease develops; furthermore, the function of host lipid mediators in macrophage death modality are addressed. The book also illustrates how the balance between prostaglandins and lipoxins determines whether infected macrophages undergo apoptosis or necrosis, which is the ultimate factor in the outcome of infection. Finally, it is a synthesis of the authors’ recent studies and the studies of others to offer a new understanding of immunity to tuberculosis.